PWE-352 Asymptomatic radiologically detected colonic perforations in the english NHS bowel cancer screening programme (NHSBCSP). (22nd June 2015) - Derbyshire, E; Nickerson, C; Hungin, A; Rutter, MD
Abstract : Introduction: Colonoscopic perforation remains one of the most serious adverse events associated with colonoscopy. Patients typically present with symptoms as a result of peritoneal irritation, however, colonic perforation may be diagnosed radiologically in patients who are entirely asymptomatic. The aims of this study were to identify cases of asymptomatic radiologically detected colonic perforation in the English NHSBCSP, describe similarities between them and explore why such perforations occur. Method: We identified all reported cases of colonoscopic perforation from the start of the NHSBCSP in 2006 up to and including 13/03/2014 from the web based database used by the NHSBCSP, the Bowel Cancer Screening System. The NHSBCSP definition of perforation is: air, luminal contents or instrumentation outside the gastrointestinal tract. Bowel Cancer Screening Centres were subsequently asked to complete an online questionnaire relating to the patient's post perforation presentation, management and outcome. Results: Of 147 perforations identified, complete data on 117 was received. Four asymptomatic radiologically detected colonic perforations were identified. Case 1 was a biopsied rectal cancer. Staging Magnetic Resonance Imaging (MRI) and staging Computed Tomography (CT) 12 and 14 days respectively following colonoscopy noted a sealed off perforation posterior to the rectum. Two cases were associated with a biopsied sigmoid cancer; one a perforation identified at staging CT 2 days following colonoscopy, the other on a same day completion CT virtual colonoscopy after the cancer was impassable endoscopically, showing gas to the right of the tumour. Case 4 was a biopsied hepatic flexure cancer with perforation diagnosed on staging CT 24 h later. TNM classification was reported in 3 cancers: T3N0M0, T4N1MO and T4N2M0. Histology confirmed well/moderately differentiated adenocarcinoma in 3 cancers. Two of these patients were recalled to hospital following CT findings, subsequently having surgery. The other 2 did not require immediate admission. Conclusion: All asymptomatic radiologically detected perforations were associated with colorectal cancer seen on staging radiological investigation. It is likely that only perforations associated with cancer will present asymptomatically as it is only they that have staging radiological investigation. TNM classification was at least T3. Emergency surgery was not required in three of these patients. The underlying cause of this sub group of perforations is perhaps more likely to be due to invasion of the cancer and not biopsy of it, however, a larger case series is required to confirm these findings. Disclosure of interest: None Declared.